2012
DOI: 10.1111/jace.12066
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Microwave Annealing of Amorphous Lead Zirconate Titanate Thin Films Deposited by Sol‐Gel Method on LaNiO3/SiO2/Si Substrates

Abstract: The heating behavior of LaNiO3 (LNO) films on SiO2/Si substrate heated by 2.45 GHz microwave irradiation in the microwave magnetic field was first investigated, and then amorphous Pb(Zr0.52Ti0.48)O3 (PZT) thin films were deposited on LNO‐coated SiO2/Si substrates by a sol‐gel method and crystallized in the microwave magnetic field. The crystalline phases and microstructures as well as the electrical properties of the PZT films were investigated as a function of the elevated temperature generated by microwave i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…It has been reported that amorphous oxide films on the Pt/Ti/SiO 2 /Si substrate, such as PZT, LaNiO 3 and PbTiO 3 films, can be crystallized into the perovskite phase in a short time by microwave radiation because the crystallization process under microwave radiation is different from the conventional crystallization process. 26,28,31 In the process of microwave radiation, the heat mainly comes from the interaction between bottom electrode and silicon substrate and microwave. 32 Therefore, the heat flows from the film/substrate interface to the film surface during the microwave radiation process.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that amorphous oxide films on the Pt/Ti/SiO 2 /Si substrate, such as PZT, LaNiO 3 and PbTiO 3 films, can be crystallized into the perovskite phase in a short time by microwave radiation because the crystallization process under microwave radiation is different from the conventional crystallization process. 26,28,31 In the process of microwave radiation, the heat mainly comes from the interaction between bottom electrode and silicon substrate and microwave. 32 Therefore, the heat flows from the film/substrate interface to the film surface during the microwave radiation process.…”
Section: Resultsmentioning
confidence: 99%
“…[24][25][26][27][28][29] Compared to ordinary heating, microwave radiation could achieve perovskite Pb(Zr,Ti) O 3 (PZT) lms with good ferroelectric properties in a short-time or at low-temperatures, because it could reduce the potential barrier of phase transition from amorphous to perovskite phase during the crystallization process. [24][25][26] Moreover, microwave radiation can change the microstructure and density of the ferroelectric lms, because the crystallization process (the nucleation and growth of perovskite grains) under microwave radiation is different from that of ordinary heating. 25,28 At present, the crystallization process of AFE thin lms under microwave radiation has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The results in publications and in our lab have illustrated that the combination of microwave heating and Ni catalysts can give rise to conversions of both CO 2 and CH 4 in DRM 4, 27. LaNiO 3 is a strong microwave receptor, and can be effectively heated under microwave irradiation 28, 29.…”
Section: Introductionmentioning
confidence: 81%
“…However, columnar grain growth in LNO films is challenging. Most of the authors who studied the CSD of LNO films on substrates of various structures reported films with a porous, polycrystalline structure and fine equiaxed grains [ 19 , 24 , 41 , 42 ]. The defective structure causes enhanced resistivity, and it is not optimal for growing on the ferroelectric perovskite layer or other functional heterostructures [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Columnar grain growth in CSD films is usually caused by heterogeneous nucleation at the film–substrate interface [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ]. For this reason, the main strategy of columnar grain growth in CSD films is a choice of the substrate with a close lattice constant or introducing an intermediate seeding layer whose structure decreases the Gibbs free energy Δ Gv at the interface [ 32 , 46 , 47 ].…”
Section: Introductionmentioning
confidence: 99%